The Therapeutic Effect of Active Vitamin D Supplementation in Preventing the Progression of Diabetic Nephropathy in a Diabetic Mouse Model - Nakhoul, Nakhoul (J Diabetes Res, 2020)
BACKGROUND: Diabetic nephropathy (DN) is one of the most common microvascular complications of diabetes and is the leading cause of end-stage renal disease (ESRD) and replacement therapy worldwide. Vitamin D levels in DN patients are very low due to the decrease in the synthesis and activity of 1-α hydroxylase in the proximal tubule cells and decrease in the vitamin D receptor abundance. To date, few studies have shown the antioxidant effects of 1α,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] on hyperglycemia-induced renal injury. The selective activator of the vitamin D receptor, paricalcitol, reduces proteinuria and slows the progression of kidney injury. The precise mechanism through which vitamin D affects diabetic status and provides kidney protection remains to be determined. METHODS: Diabetes mellitus (DM) was induced in 94 8-week-old DBA/2J mice by intraperitoneal injection of streptozotocin (STZ). DM mice were randomly divided into receiving vehicle or treatment with paricalcitol, the active vitamin D analog, 1 week after DM induction or paricalcitol treatment 3 weeks after DM induction. An additional control group of healthy wild-type mice was not treated. Urine albumin, blood urea nitrogen, and creatinine levels were measured before and at the end of the paricalcitol treatment. Periodic acid-Schiff, immunohistochemistry staining, and western blot of the renal tissues of vitamin D receptor, villin, nephrin, and podocin expressions, were analyzed. RESULTS: Paricalcitol treatment restored villin, nephrin, and podocin protein levels that were downregulated upon DM induction, and reduced fibronectin protein level. Vitamin D receptor activation by paricalcitol may reduce proteinuria of DN in mice and alleviate high-glucose-induced injury of kidney podocytes by regulating the key molecules such nephrin-podocin. CONCLUSIONS: Paricalcitol treatment was associated with improved structural changes in type 1 diabetic mice including upregulation of vitamin D receptor expression, and decreased fibrosis markers such as fibronectin. These effects may contribute to the consistent benefit of vitamin D analog to slow the deterioration in glomerular function and reduce the risk of ESRD in patients with type 1 and 2 diabetes mellitus. Our results suggest that additional use of paricalcitol may be beneficial in treating patients with diabetes under standard therapeutic strategies.